2020
DOI: 10.7717/peerj.9572
|View full text |Cite
|
Sign up to set email alerts
|

Epitope-based chimeric peptide vaccine design against S, M and E proteins of SARS-CoV-2 etiologic agent of global pandemic COVID-19: an in silico approach

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the etiologic agent of the ongoing pandemic of coronavirus disease 2019 (COVID-19), a public health emergency of international concerns declared by the World Health Organization (WHO). An immuno-informatics approach along with comparative genomics was applied to design a multi-epitope-based peptide vaccine against SARS-CoV-2 combining the antigenic epitopes of the S, M, and E proteins. The tertiary structure was predicted, refined and validated us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(82 citation statements)
references
References 74 publications
1
81
0
Order By: Relevance
“…Although this was designed, and multiple amino acids from the 3 epitopes in the NOM protein are contributing to the binding to TLR4, it shows that components of SARS-COV-2 are binding well to TLR4 and raises further questions. More recently, several other in silico studies have designed multiepitope vaccines using SARS-CoV-2 spike glycoprotein constructs/subunits, and they are found to bind TLR4 using molecular docking studies (see [ 115 119 ]).…”
Section: Evidence For Sars-cov-1 and Sars-cov-2 Proteins Binding Tmentioning
confidence: 99%
“…Although this was designed, and multiple amino acids from the 3 epitopes in the NOM protein are contributing to the binding to TLR4, it shows that components of SARS-COV-2 are binding well to TLR4 and raises further questions. More recently, several other in silico studies have designed multiepitope vaccines using SARS-CoV-2 spike glycoprotein constructs/subunits, and they are found to bind TLR4 using molecular docking studies (see [ 115 119 ]).…”
Section: Evidence For Sars-cov-1 and Sars-cov-2 Proteins Binding Tmentioning
confidence: 99%
“…In order to find out the impact of identified mutations and their implications on vaccine development, we have investigated the reported vaccine candidates from previous studies [ 51 , 52 , 53 , 54 , 55 , 56 ]. The identified mutations in the structural proteins were mapped with these vaccine candidates and it was found that 23 mutations in S protein, 1 in E, 2 from M, and 7 from N protein were observed to map with the reported B-cell and T-cell epitopes ( Supplementary File S9 ).…”
Section: Resultsmentioning
confidence: 99%
“…Antigenic properties of spike glycoprotein were more focused by theory and experimental researchers [20][21][22] . Applying this basic knowledge, a number of peptide-based designs have been presented to date, which encompass those integrating epitopes from a single or few viral protein(s) [23][24][25][26][27] to those considering the whole proteome of the virus 28 . The present research contributes to current understanding in this field by offering an alternative approach for developing a potential COVID-19 vaccine, where the entire set of structural proteins were searched for most efficacious epitopic segments.…”
Section: Discussionmentioning
confidence: 99%
“…Triggering TLR-3 may help induce the TLR signalling networks which activate the immune pathways evolved specifically against viral pathogens. In addition, this TLR choice was a consensus from vaccine design research works on viral/retroviral pathogens, specifically coronavirus species 12 , 14 , 25 , 26 , 42 , 43 . While we note that other Toll-like immune receptors such as TLR-2, -4, -5, -7 and -8 may be stimulated by the COVID-19 virus, they were not considered here as their exact roles are not established, with some possibly functioning even to the advantage of the coronavirus 44 , 45 .…”
Section: Discussionmentioning
confidence: 99%